ОПЫТ ДИСТАНЦИОННОГО ОБУЧЕНИЯ СОЦИАЛЬНО-ЭКОНОМИЧЕСКОЙ КАРТОГРАФИИ - Кислова (Kislova Veronika), Вероника Александровна (Географический вестник=Geographical bulletin, 2017)
Рассматриваются модели дистанционного обучения (ДО) картографии в мире. В качестве примера приводится разрабатываемый в настоящее время курс дистанционного обучения «Социально-экономическое картографирование». Определяются основные цели, задачи и требования, предъявляемые к курсу по картографии, описываются основные его структурные блоки (теоретический, проверочных работ, заключительной проверки полученных знаний), рассматривается его реализация с помощью специального программного обеспечения в сети Интернет. THE EXPERIENCE OF E-LEARNING EDUCATION OF SOCIAL-ECONOMIC MAPPING E-learning (EL) is based on the high computer and the Internet technologies including the GIS, multimedia, video conference. This is a new perspective stream of the cartography. «The social-economic mapping» is posed as an EL course. This e-course is based on the state-of-art models of EL, including the special software. The course is composed of three main blocks: theoretic material, training exercises, and final test. Block of theoretical material consists of the basic knowledge needed for each part of the course. Rich sign diversity (picture signs, linear signs, qualitative background, and areas) and a broad spectrum of computer programs are typically used for the social-economic mapping. It is necessary to add the Block of theoretical material graphic dates. The block of the training exercises consists of practical tasks. They concentrate on the providing of the control of knowledge assimilation of the theoretical part of the course. Tasks are presented by both tests and small practical tasks focusing on description of the social-economic maps. The results of the final test have to demonstrate the quality of the understanding and level of assimilation of EL material by the students.